2018
DOI: 10.7150/ijbs.23946
|View full text |Cite
|
Sign up to set email alerts
|

CTGF Contributes to the Development of Posterior Capsule Opacification: an in vitro and in vivo study

Abstract: Connective tissue growth factor (CTGF) is a crucial factor that plays a major role in the process of posterior capsule opacification (PCO). However, the effects of CTGF on the proliferation and migration of lens epithelial cells (LECs) and on the mechanism of the epithelial mesenchymal transition (EMT) and extracellular matrix (ECM) in human lens epithelial cells (HLECs) as well as the effects of shRNA-mediated CTGF knockdown on the development of PCO in rats remain unclear. In the present study, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 48 publications
(39 reference statements)
1
15
0
Order By: Relevance
“…Ten eyes of five pigs were obtained from an abattoir. The porn capsular bag model was created as described in our previous study [25]. The capsular bags, which were treated with gremlin at 200 μg/L or control medium, were incubated in MEM medium (CM10010, M&C Gene Technology Ltd., China) for 14 days in an incubator of 5% CO 2 at 38°C.…”
Section: Preparation Of Capsular Bag Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten eyes of five pigs were obtained from an abattoir. The porn capsular bag model was created as described in our previous study [25]. The capsular bags, which were treated with gremlin at 200 μg/L or control medium, were incubated in MEM medium (CM10010, M&C Gene Technology Ltd., China) for 14 days in an incubator of 5% CO 2 at 38°C.…”
Section: Preparation Of Capsular Bag Modelmentioning
confidence: 99%
“…The transwell migration assay and Wound healing assay were performed to identify and evaluate the chemical cues of gremlin on cell migration as described in our previous study [25]. Briefly, in the transwell assay, 10 4 cells were seeded in the upper chamber and serumfree medium with or without containing 200 μg/ L gremlin was placed in the bottom compartment.…”
Section: Wound Healing Assay and Transwell® Migration Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that TGF-β2 played an essential role in the formation of PCO via the canonical TGF-β/Smad signaling pathway, as well as via non-canonical signaling [ 20 , 46 ]. Activation of the ERK signaling pathway was involved in cell carcinogenesis, cancer cell metastasis, and a series of fibrotic diseases, including PCO [ 26 , 47 , 48 ]. Our study revealed the critical role of the ERK signaling pathway in the TGF-β2-induced EMT of human LECs.…”
Section: Discussionmentioning
confidence: 99%
“…Wound healing and Transwell ® migration assay were performed as described in our previous study (Ma, Jing, et al., ). The cells were in serum‐free medium containing 10 μg/L IL‐2 with or without WP1066 (S2796; Selleck) or BAY 11‐7082 (S2913; Selleck).…”
Section: Methodsmentioning
confidence: 99%